To solve the equation \( 3x - 3 = 6x + 18 \), follow these steps:
-
Start with the original equation: \[ 3x - 3 = 6x + 18 \]
-
Rearrange the equation to get all terms involving \( x \) on one side and constant terms on the other side. Subtract \( 3x \) from both sides: \[ -3 = 6x - 3x + 18 \] Which simplifies to: \[ -3 = 3x + 18 \]
-
Next, subtract \( 18 \) from both sides: \[ -3 - 18 = 3x \] This simplifies to: \[ -21 = 3x \]
-
Finally, divide by \( 3 \): \[ x = -7 \]
Thus, the solution is \( x = -7 \).
The final answer is: x = −7.